2022
DOI: 10.4045/tidsskr.22.0156
|View full text |Cite
|
Sign up to set email alerts
|

Ethical dilemmas for nursing home doctors during the COVID-19 pandemic

Abstract: Bergen senter for etikk og prioritering (BCEPS) Institu for global helse og samfunnsmedisin Universitetet i Bergen Forfa erbidrag: utforming av idé, utforming av studien, datainnsamling, analyse av datamaterialet, li eratursøk, hovedansvar for utarbeiding og revisjon av manus og godkjenning av innsendte manusversjon. Emily McLean er lege og stipendiat. Forfa eren har fylt ut ICMJE-skjemaet og oppgir ingen interessekonflikter.Bergen senter for etikk og prioritering (BCEPS) Institu for global helse og samfunnsme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…This is in line with results from McLean et al. [ 29 ], who found that physicians in Norway working in nursing homes during the COVID-19 pandemic experienced difficulties in prioritizing care. The emphasized moral distress perceived during the pandemic could in part be attributed to the shortage of hospital beds, which might have impacted the medical decisions made in nursing homes, thus resulting in another aspect of restricting care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with results from McLean et al. [ 29 ], who found that physicians in Norway working in nursing homes during the COVID-19 pandemic experienced difficulties in prioritizing care. The emphasized moral distress perceived during the pandemic could in part be attributed to the shortage of hospital beds, which might have impacted the medical decisions made in nursing homes, thus resulting in another aspect of restricting care.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, McLean et al. [ 29 ] found that physicians experienced ethical challenges, due to the conflicts involved in providing good care to one resident while trying to protect others.…”
Section: Discussionmentioning
confidence: 99%
“… 24 This has created heterogeneity across NHs, triggering also ethical dilemmas among HCPs, for example, regarding the implications on residents, or the need to make choices sometimes against the recommendations. 38 …”
Section: Discussionmentioning
confidence: 99%
“…Risk Management and Healthcare Policy 2022:15 triggering also ethical dilemmas among HCPs, for example, regarding the implications on residents, or the need to make choices sometimes against the recommendations. 38 At first, NHs focused on interventions at environmental levels, mainly implementing national and/or regional guidelines 13,[29][30][31] and available evidence. 21,22,27,37 Visitors' restrictions (including volunteers) were implemented immediately, and compartmentalization was applied in all NHs, whereas other interventions (eg, quarantine area for residents returning from hospital, dressing rooms for staff) were implemented in only some.…”
Section: Dovepressmentioning
confidence: 99%